(untitled) (Asian Journal of Medical and Biological Research, 2015)
The study was conducted at Upazila Livestock Development Centre, Kapasia, Gazipur, during July, 2011 to December, 2011 to identify and determine the prevalence of clinical diseases and disorders of goats. A total number of 488 clinical cases of goats were recorded. Diagnosis of the clinical cases of goats were based on general examination (history and owners complaint), physical examination of patient (inspection, palpation and percussion), clinical examination, microscopic examination and using common laboratory techniques. The clinical cases were divided into three groups on the basis of treatment required-medicinal, gynaeco-obstetrical and surgical cases. Among the three types of cases, medicinal cases 428(87.72%) were highest followed surgical cases 43(8.80%) and gynaeco-obstetrical cases 17(3.48%). Among the medicinal cases of goats, the contagious diseases PPR 32(6.56%), black quarter 23(4.73%) fascioliasis 77(15.78%), diarrhoea 35(7.17%), dysentery 30(6.15%), ectoparasitism 30(6.15%), paramphistomiasis 25(5.12%), gastrointestinal nematodiasis 21(4.3%), fever 20(4.1%) were recorded major disease problems in goats. Among the gynaeco-obstetrical cases, retained placenta 5(1.02%) and repeat breeding 12(2.46 %) were recorded as major gynaeco-obstetrical problems in goats. Abscess 9(1.84 %), castration 4(0.81%), myiasis 10(2.05%), navel-ill 7(1.43%), gid disease 2(0.41%), urolithiasis 5(1.02%) and fracture 6(1.23%) were recognized as the main disorders which required surgical interventions. It may conclude that a number of diseases have been occurring in goats at study area and this report may help to develop strategies against major diseases reported in this study. Asian J. Med. Biol. Res. June 2015, 1(1): 47-52